The brain protection of MLKL inhibitor necrosulfonamide against focal ischemia/reperfusion injury associating with blocking the nucleus and nuclear envelope translocation of MLKL and RIP3K - Zhou, Xian-Yong; Lin, Bo; Chen, Wei; Cao, Rui-Qi; Guo, Yi; Said, Ali; Khan, Taous; Zhang, Hui-Ling; Zhu, Yong-Ming (Frontiers in Pharmacology, 2023)
Mixed lineage kinase like protein (MLKL) is a key mediator of necroptosis. While previous studies highlighted the important role of MLKL as one of the central regulators of brain damage against acute ischemic neuronal injury, how the activation of MLKL mediates brain injuries and cell death remains unclear, especially in astrocytes. In a transient middle cerebral artery occlusion (tMCAO) rat model in vivo, and an oxygen-glucose deprivation and reoxygenation (OGD/Re) injury model in both primary cultured astrocytes and human astrocytes, we show that necrosulfonamide (NSA), a MLKL specific inhibitor, reduces infarction volume and improves neurological deficits in tMCAO-treated rats. In addition, NSA treatment, as well as RIP1K inhibitor Nec-1 or RIP3K inhibitor GSK-872 treatment, decreases the OGD/Re-induced leakage of LDH in both primary cultured astrocytes and human astrocytes. NSA treatment also reduces the number of propidium iodide (PI)-positive cells, and prevents the upregulation of necroptotic biomarkers such as MLKL/p-MLKL, RIP3K/p-RIP3K, and RIP1K/p-RIP1K in ischemic penumbra of cerebral cortex in tMCAO-treated rats or in OGD/Re-treated human astrocytes. Importantly, NSA treatment blocks both the nucleus and nuclear envelope localization of MLKL/p-MLKL and RIP3K/p-RIP3K in ischemic cerebral cortex induced by tMCAO. Similarly, Co-immunoprecipitation assay shows that NSA treatment decreases tMCAO- or OGD/Re- induced increased combination of MLKL and RIP3K in nuclear envelope of ischemic penumbra of cerebral cortex or of primary cultured astrocytes, respectively. RIP3K inhibitor GSK-872 also reduces tMCAO-induced increased combination of MLKL and RIP3K in nuclear envelope of ischemic penumbra of cerebral cortex. These data suggest NSA exerts protective effects against focal ischemia/reperfusion injury via inhibiting astrocytic necroptosis through preventing the upregulation of necroptotic kinases as well as blocking both the nucleus and nuclear envelope co-localization of p-MLKL and p-RIP3K. The translocation of p-MLKL, along with p-RIP3K, to the nuclear envelope and the nucleus may play a crucial role in MLKL-mediated necroptosis under ischemic conditions.